2016
DOI: 10.1007/978-3-319-40229-1_9
|View full text |Cite
|
Sign up to set email alerts
|

Fast Cube Tests for LIA Constraint Solving

Abstract: We present two tests that solve linear integer arithmetic constraints. These tests are sound and efficiently find solutions for a large number of problems. While many complete methods search along the problem surface for a solution, these tests use cubes to explore the interior of the problems. The tests are especially efficient for constraints with a large number of integer solutions, e.g., those with infinite lattice width. Inside the SMT-LIB benchmarks, we have found almost one thousand problem instances wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…All these solvers employ a branch-and-bound approach with an underlying dual simplex solver [14]. The only exception is mathsat5, which, subsequent to our first publication on the unit cube test [8], now also performs the unit cube test in advance. That is why we also test mathsat5 once with the unit cube test turned on (mathsat5-3.13+uc) and once with the test turned off (mathsat5-3.13).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All these solvers employ a branch-and-bound approach with an underlying dual simplex solver [14]. The only exception is mathsat5, which, subsequent to our first publication on the unit cube test [8], now also performs the unit cube test in advance. That is why we also test mathsat5 once with the unit cube test turned on (mathsat5-3.13+uc) and once with the test turned off (mathsat5-3.13).…”
Section: Methodsmentioning
confidence: 99%
“…We were able to develop several techniques based on this transformation that allow us to investigate linear arithmetic constraints in various ways. Here, we present our previous results [7,8] on the linear cube transformation in more detail as well as some new applications (e.g., quantifier elimination).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even so, not all unbounded systems are equally difficult. For instance, a system where all directions are unbounded has always a mixed solution: Lemma 5 (Absolutely Unbounded [9]). If all directions are unbounded in a constraint system Ax ≤ b, then the constraint system has an integer solution.…”
Section: Preliminariesmentioning
confidence: 99%
“…Furthermore, in contrast to the previous solver, it now supports an integration with non-linear polynomial arithmetic which is complete for signature disjoint theory combinations. One of the deciding factors in leapfrogging the previous solver in number of benchmarks solved included so far an integration with the method by Bromberger and Weidenbach [3], [4] to detect integer feasible solutions from strengthened inequalities. We observed that the default strengthening proposed by Bromberger and Weidenbach can often be avoided: integer solutions can be guaranteed from weaker systems.…”
Section: Introductionmentioning
confidence: 99%